2021
DOI: 10.1155/2021/5363750
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in Encrypted Internet Traffic Using Hybrid Deep Learning

Abstract: An increasing number of Internet application services are relying on encrypted traffic to offer adequate consumer privacy. Anomaly detection in encrypted traffic to circumvent and mitigate cyber security threats is, however, an open and ongoing research challenge due to the limitation of existing traffic classification techniques. Deep learning is emerging as a promising paradigm, allowing reduction in manual determination of feature set to increase classification accuracy. The present work develops a deep lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The experimental results showed that the proposed HNNIM model achieves the average accuracy of 89.28% on the multiclassification task, which was higher than other classifiers. Similar work was carried out by researchers in [26] by proposing a hybrid DL model to classify and detect enciphered network traffic. The CNN and gated recurrent unit (GRU) were used together for rapid feature extraction and learning.…”
Section: Deep Learning Based Techniquesmentioning
confidence: 80%
“…The experimental results showed that the proposed HNNIM model achieves the average accuracy of 89.28% on the multiclassification task, which was higher than other classifiers. Similar work was carried out by researchers in [26] by proposing a hybrid DL model to classify and detect enciphered network traffic. The CNN and gated recurrent unit (GRU) were used together for rapid feature extraction and learning.…”
Section: Deep Learning Based Techniquesmentioning
confidence: 80%
“…Traditional machine learning techniques including Iterative Dichotomiser 3 (ID3), decision tree (C 5.0), classification and regression tree (CART), and artificial neural network (ANN) have been previously recommended to provide a measure of security for IoBNT biocyber interfaces [25,26]. Deep learning is a sub-field of traditional machine learning, providing increased flexibility and accuracy over classical learning algorithms, and offering the ability to incrementally learn and extrapolate new features from a limited set of training data [34,35]. Moreover, the thin and layered structure of sequential deep neural network models makes them ideal for being deployed over a low-powered and resource-constrained bio-cyber interface, still facilitating real-time anomaly detection.…”
Section: Deep-learning Enabled Traffic Analysismentioning
confidence: 99%
“…Convolutional neural network (CNN) is an extension of the traditional feed-forward neural network. CNN has been proven significantlyly successful in image processing tasks including object identification in robotics, and self-driven cars, and are now gaining traction in cyber security application particularly anomaly detection [32,[34][35][36]. Four main operations of CNN comprise of a convolution layer responsible for feature extraction, a non-linear activation function such as Rectified Linear Unit (ReLu) for fast(er) model learning, a pooling layer for generalization, and a fully connected layer (to be used for classification) [37].…”
Section: Deep-learning Enabled Traffic Analysismentioning
confidence: 99%
“…Anomaly detection has been widely used in various fields, including cyber security [ 13 , 14 ], communications security [ 15 , 16 , 17 ], IoT [ 18 , 19 , 20 ], video surveillance [ 21 , 22 ], etc. In general, anomaly detection refers to finding special instances that differ from given normal instances.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, it is more appropriate to view the surface defect detection problem as a semi-supervised anomaly detection problem. Anomaly detection has been widely used in various fields, including cyber security [13,14], communications security [15][16][17], IoT [18][19][20], video surveillance [21,22], etc. In general, anomaly detection refers to finding special instances that differ from given normal instances.…”
Section: Introductionmentioning
confidence: 99%